Learning Listening and Reading Skills from the Arabic Language in a Psycholinguistic Perspective - Muhammad Tareh Aziz; M. Kemal Husain Al-Firdausy; Moh. Syafi'i (STAI Hubbulwathan Duri, 2022)
Psycholinguistics is important science to learn to provide interesting and enjoyable learning outcomes for students. Psycholinguistics and the Arabic Language have a very close relationship to achieving learning objectives. Very weak, this is certainly due to the lack of interest in learning and lack of motivation from students. Therefore, this study uses Psycholinguistics as a theory, especially in the book “How Language is Learned” to analyze a problem that exists in learning Arabic. This research was conducted using a descriptive qualitative approach with data collection methods: Observation, Interviews, and Documentation. External factors affect the listening and reading abilities of the students of At-Thoyyibiyah Bangkalan school. The solution to overcome these problems is to provide motivation and encouragement to students which can be done by their parents by memorizing vocabulary, forming a language environment, and using film media in increasing student motivation in listening learning.